Local variation in stress response of juvenile anadromous brown trout, Salmo trutta - Madeleine Berry; Lucas A. Zena; Jonathan A. C. Roques; Erik Sandblom; Eva B. Thorstad; Johan Höjesjö (Ecology and Evolution, 2024)
Abstract Habitat fragmentation may cut off anadromous salmonids from parts of their potential native habitat and separate previously connected populations. Understanding the consequences of this is vital for fish management and prioritization of restoration activities. Here, we show that there is a significant difference in the body morphology, physiological stress response, and aspects contributing to aerobic capacity between juvenile anadromous brown trout, Salmo trutta, collected at a downstream site and an upstream site, separated by 2 km and several challenging stream sections, in a small unfragmented stream system in western Sweden. Following a standardized stress test, there were significant differences between fish from the upstream and downstream sites (plasma cortisol concentration, plasma osmolality, hematocrit, hemoglobin concentration, and mean corpuscular hemoglobin concentration). Plasma glucose concentration did not significantly differ between fish from the two sites. Fish from the upstream site had larger spleen mass, although there was no evidence of differences in ventricle mass or proportion of compact ventricular myocardium. These physiological differences indicate local variation in stress response and highlight the importance of considering local trait variation in river management. If a section of the river becomes fragmented or degraded, and there are differences in the juveniles in different parts of the river, the consequence for the population might be larger than the proportional loss of habitat.